EXPLORATORY NOTE ON CONSUMPTION AND SOCIOECONOMIC CLASSIFICATION IN BRAZIL BASED ON EVIDENCES FROM THE FAMILY EXPENDITURE SURVEY - Guilherme França dos Santos Paiva (Revista de Economia Contemporânea)
ABSTRACT The present study aims at analysing different stratification criteria used in Brazil by market research companies and academia, taking into account family profiles based on socioeconomic and demographic variables. It presents different strata profiles generated by two nationally well-known stratification criteria based on survey data from the two last editions of the Brazilian Family Expenditure Survey (2002/2003 and 2008/2009)and it also provides evidence on patterns of change over time. The evidence corroborates that an economic improvement took place from 2003 to 2009 for those individuals classified in the lower socioeconomic stratum, together with an increase of total and per capita average income, and an increase of expenses. On the other hand, a visible reduction of savings for families in all economic strata and higher levels of household indebtedness was also noticed.